Evaluasi Program Halaqah Al-Qur’an dengan Discrepancy Evaluation Model dalam Pembinaan Santriwati di SMP TQ Muadz bin Jabal Albredi Boarding School Kendari - Arif, Dwi Rizky Agrina; Nurlathifah Thulfitrah B (Jurnal Pendidikan Dirgantara, 2026)
This study is motivated by the importance of systematic evaluation in ensuring the quality and effectiveness of the implementation of educational programs, particularly the Al-Qur'an Halaqah Program as a means of developing the ability to read and memorize the Al-Qur'an and shaping the religious character of female students. This study aims to identify the gap between the established standards and the actual implementation of the program using the Discrepancy Evaluation Model (DEM). The approach used is qualitative evaluative with five stages of evaluation, namely design, installation, process, product, and comparison. Data was obtained through interviews, observations, and documentation studies, then analyzed through the stages of data collection, processing, presentation, and conclusion drawing using triangulation techniques. The results showed that the design and installation stages met the standards, while in the process stage, a gap was found in the consistency of female student attendance. In the product stage, the success rate reached 93.48%, but there was still an imbalance in memorization achievement. The implication is that the program should be continued with strengthened attendance monitoring and individual mentoring strategies to improve the equity of outcomes and the sustainability of the program.